An Enablers Modeling Analysis Intended for Effective Implementation of Lean Six Sigma in Indian Manufacturing Industries - Abhijeet A. Shahade (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Industrial enterprises have found it challenging to thrive due to a scarcity of natural resources, shifting customer needs, and intense global competition. Manufacturing businesses need to think outside the box in order to solve these challenges. Lean Six Sigma is one of the main business methods used by manufacturing businesses to improve operational performance. Lean Six Sigma has been one of the main business methods employed by Indian manufacturing organizations to improve operational performance. Any industrial organization that wants to apply lean six sigma sustainably must identify its enablers. The purpose of the current study is to identify and evaluate Lean Six Sigma enablers that are Sustainable. Studies are what motivated the current case study because there hasn’t been any prior research on sustainable Lean Six Sigma in Indian manufacturing businesses. Using a numerical approach, this paper aids in identifying and prioritizing the elements that support the successful implementation of Lean Six Sigma in the Indian manufacturing sector. Implementation specialists and practitioners will be able to focus on enabling the most significant dominating enablers and deliver LSS adoption with sustainable considerations thanks to this Integrated Modeling Analysis approach.